1990
DOI: 10.1017/s0021859600073883
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of crop yields and soil conditions during 30 years under annual tillage or grazed pasture

Abstract: Crop yields and soil properties of grazed grass-clover pasture and arable plots at the Grasslands Research Institute, Hurley, UK. were measured over 30 years . Yields of herbage declined from 9-6 t DM/ha in the first harvest year to 4-6 t in years 5 to 8 but subsequently increased (after liming) to give a mean yield of 8-2 t for 1963-84. Yields of barley in plots receiving a seed-bed application of 45 kg N/ha averaged (1962-80) 31 t/ha and, in plots top dressed with an additional 100 kg N/ha, 41 t/ha but after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 18 publications
4
13
0
Order By: Relevance
“…Our values are in the middle to upper end of the range of N-turnover rates reported in the literature e.g. 1-3% (Bremner, 1965), 2.5% (Tyson et al, 1990), 3.6% (Macduff and White, 1985), 2-6% (Hassink et al, 1990), 3-7.5% (Ball and Ryden, 1984), and up to 10% , assessed by various techniques for different soil types.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Our values are in the middle to upper end of the range of N-turnover rates reported in the literature e.g. 1-3% (Bremner, 1965), 2.5% (Tyson et al, 1990), 3.6% (Macduff and White, 1985), 2-6% (Hassink et al, 1990), 3-7.5% (Ball and Ryden, 1984), and up to 10% , assessed by various techniques for different soil types.…”
Section: Discussionsupporting
confidence: 53%
“…In another study, also on Frilsham soil, the N content of the soil under a grazed grass/clover sward reached an equilibrium after approximately 10 years (Tyson et al, 1990), so that the high value which we obtained for net mineralization with GC (415 kg N ha -1) may be a feature of a well-established mixed sward. Certainly, high productivity has been achieved from unfertilized mixed swards grazed by sheep (Parsons et al, 1991) which was attributed to rapid cycling of relatively large quantities of N through the soil/ plant/animal system: mineralization rates comparable to those in our study may have contributed to this rapid cycling.…”
Section: Discussionsupporting
confidence: 52%
“…Tyson et al (1990) found that changing land use from more or less continuous cereals to pasture increased soil organic carbon from 1.2 to 1.8% in 10 years, with soil N increasing from 0.13 to 0.17%. The annual increments in soil C and N were 1000 and 75 kg ha K1 , respectively.…”
Section: Rotationsmentioning
confidence: 99%
“…Stubbles of less than five years contain about 40-80 kg N ha -1 and this amount does not significantly increase with ageing (Davies et al 2001;Whitehead et al 1990). The N content of the soil organic matter of grassland increases approximately linearly in young grasslands (\10 years), ranging from 20 to 130 kg N ha -1 year -1 (Cuttle and Scholefield 1995;Hassink 1994;Tyson et al 1990;Whitehead et al 1990). The accumulation of organic matter levels off during ageing and may continue for more than 30-100 years (Jenkinson 1988).…”
Section: Introductionmentioning
confidence: 99%